HIBRIDITAS KEISLAMAN GENERASI Z DAN FENOMENA HIJRAH POP - Sunaryanto; Ahmad Rofi Syamsuri (LP2M IAI Miftahul Ulum Pamekasan, 2022)
This study analyzes the meaning of Islamic hybridity and the phenomenon of pop hijrah among Generation Z. This research is qualitative research with literature study, the primary data is collected from journals, books, and internet sources and others. The conclusion of this study is that the hybrid identity of generation Z is the result of negotiations in the third space (read: popular mass media) between Islam and popular culture. The Hijrah Pop identity is a hybrid identity resulting from a cross between Islam and popular culture. Generation Z hybrid identity and the Hijrah Pop phenomenon are negotiated, formed, and expressed through the third space, namely social media. The hijrah, which is part of the Islamic identity of generation Z and the hijrah artist, is negotiated, formed, and expressed in the third space, namely social media. In this third space, all aspects of identity negotiate with each other as well as fight over each other. Thus, a hybrid identity was formed which actually experienced a confusion of directions. Generation Z and this hijrah artist do not yet understand which identity belongs to him. Their Islam is actually also driven by the globalization of culture and the global economy.